Case Report: A rare case of MET-amplified gastric cancer with systemic metastasis: remarkable efficacy of crizotinib and the role of precision medicine - Shen, Yan; Xu, Yaxin; Sun, Jing (Frontiers in Oncology, 2025)
Gastric cancer remains one of the most prevalent gastrointestinal malignancies, with certain subtypes, such as poorly cohesive carcinoma—including signet ring cell carcinoma (SRCC)—exhibiting aggressive progression and poor prognosis. Mesenchymal epithelial transition (MET) amplification, a relatively rare oncogenic driver in gastric cancer (~2–10.2% of cases), has been associated with resistance to conventional therapies and dismal survival (median <6 months in metastatic cases). While MET inhibitors such as crizotinib have shown efficacy in MET-altered non-small cell lung cancer (NSCLC), their role in gastric cancer remains uncertain due to tumor heterogeneity and the lack of robust clinical evidence. We report a case of a female patient with MET-amplified metastatic gastric cancer and systemic bone marrow involvement. Despite eventual disease progression, the initial response to crizotinib was remarkable, with rapid hematologic recovery (platelets: 7→216×109/L) and significant tumor regression. Although disease progression occurred after 5 months, characterized by pulmonary metastasis, biliary obstruction and multiple infections, the substantial initial benefits of crizotinib cannot be overlooked. The patient survived 8 months from diagnosis, highlighting the transient efficacy of MET inhibition and the impact of clonal evolution. This case underscores the potential and limitations of MET inhibitors in gastric cancer. Biomarker-driven selection, early resistance detection, and trials exploring crizotinib-chemotherapy/immunotherapy combinations are urgently needed to improve outcomes in this aggressive subtype.